SPONTANEOUS PLATELET AGGREGATION IN THIRD TRIMESTER PREGNANCY AT ADAM MALIK HOSPITAL, MEDAN - Rezqi Maulani Jusuf; Hotma Partogi Pasaribu; Herman Hariman (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Spontaneous Platelet Aggregation (SPA) is a condition when spontaneously platelet aggregate in plasma left in a tube at room temperature for 2-3 hours without adding any agonists. It is not entirely sure why this phenomenon happens. Pregnant females have a more tendency of hypercoagulability. Nevertheless, SPA demonstrates hyper aggregation of platelet and not the coagulation pathway. So far, there is no report regarding this phenomenon in pregnant females. This study aimed to find out whether pregnant females, especially in the third-trimester of the pregnancy, had the tendency of SPA. This cross-sectional study was established in the Department of Clinical Pathology and Department of Obstetrics-Gynecology, Adam Malik General Hospital in Medan between January–March 2016. Twenty-six females were included. Ultrasonography (USG) was used to know the age of pregnancy. From 26 females in this study, 10 were pregnant females in the third-trimester of pregnancy while 16 others were normal non-pregnant females as controls, with a mean age of 29.2±2.78 years old and 36.5±4.63 years old. There were significant differences between platelet aggregation using ADP agonist in pregnant females and controls (p <0.01). In the median Tmax 10%, there were no significant differences between platelet aggregation without ADP agonist in pregnant females and controls after 3 hours (p >0.05). Hyper aggregation and hypercoagulability in the third-trimester pregnancy tend to develop SPA. Even though there are only mild signs and symptoms, it can be an arising risk of thrombus.